Penerapan Big Data dalam Pemasaran Digital: Studi Kasus pada Industri E-commerce di Indonesia - Diva Viola Natasya Hasibuan; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
The application of big data technology has become increasingly important in the context of digital marketing, especially in the e-commerce industry in Indonesia. Faced with intense competition and increasingly diverse consumer demands, e-commerce companies in Indonesia are increasingly relying on big data to gain deep insights into consumer behavior and market trends. This study aims to explore the application of big data in digital marketing, focusing on the e-commerce industry in Indonesia. Analyzing how e-commerce companies use big data to optimize their marketing strategies, enhance personalized services, and identify new market opportunities. We also evaluate the challenges faced in implementing big data technology in the context of digital marketing in Indonesia, including issues of data privacy, security, and infrastructure.